ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONDISI FINANCIAL DISTRESS (STUDI EMPIRIS PERUSAHAAN SUBSEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020) - Yunas, Shafa Kamila; Bawono, Andi Dwi Bayu (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
Financial Distress is a condition where a company is in an unsafe condition or experiencing financial difficulties because it cannot meet its obligations at maturity. Financial Distress can occur due to several factors, one of which is the amount of debt and corporate obligations that are increasing so that the company experiences losses. This study aims to determine the influence of liquidity, profitability, leverage, intellectual capital and working capital to total assets on financial distress in food and beverage subsector companies using the Altman Z-Score model. The independent variables used in the study were liquidity, profitability, leverage, intellectual capital and working capital to total assets. The study used secondary data obtained from the financial statements of food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. The sample in this study was 72 (seventy-two) companies. Sampling techniques use purposive sampling techniques. The data analysis used in this study is descriptive analysis and multiple linear regression tests using IBM SPSS 25.0. Based on testing the hypothesis conducted, it can be concluded that liquidity variables have no effect on financial distress, profitability has no effect on financial distress and intellectual capital does not affect financial distress. While the variables leverage and working capital to total assets that affect financial distress.